Social impacts of peer-to-peer accommodation on host communities - Petruzzi, M.; Marques, C.; Campos, A. C. (International Journal of Tourism Research, 2023)
Peer-to-peer accommodation has recently emerged as a central focus of research in tourism and hospitality. However, research on socio-cultural impacts of peer-to-peer accommodation is fragmented. This study reviews the relevant literature on the socio-cultural impacts of peer-to-peer accommodation on host communities and proposes an integrative framework and a working definition for goal socio-cultural impacts of peer-to-peer accommodation. This literature review contributes to knowledge of how this business paradigm affects and frames host communities and integrates the factors that should be explored by researchers, policymakers, and organizations to manage the impacts of peer-to-peer accommodation on host communities.